Cardiac Contractility Modulation (CCM) Italian Registry: preliminary analysis. (19th May 2022) - Matta, M; Devecchi, C; Troccoli, R; Lupi, A; Paffoni, P; Nocerino, P; Dell'era, G; Manganelli, G; Di Belardino, N; Lucifero, A; Giudici, V; D'agostino, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cardiac contractility modulation (CCM) therapy is a treatment option for patients suffering symptomatic Chronic Heart Failure (HF) with reduced left ventricular ejection fraction (LVEF) despite optimal medical therapy (OMT) [1]. CCM, by delivering high-output electrical impulses during ventricular absolute refractory period, increases the activity of proteins involved in intracellular calcium handling. This therapy has been associated with improvement in quality of life (QoL) and reduction of HF-hospitalizations [2, 3]. Our aim is to present preliminary data from the CCM Italian Registry. Methods: The CCM Italian Registry is a prospective, observational, multicentre study investigating the long-term impact of CCM therapy in HF patients on LVEF, Minnesota Living With HF Questionnaire (MLWHFQ) and 6-minutes walking test (6MWT) [4]. Preliminary results after one year of follow-up have been analysed in this abstract. Data are expressed as median and interquartile range. Changes from baseline have been tested with Wilcoxon signed-rank test. Results: A total of 42 patients suffering HF, with LVEF<45%, NYHA class>II despite OMT, have been enrolled and implanted with CCM device in 10 Centres. Most of patients were male (41 patients, 98%), with a median age of 76 years (70-79). The most frequent aetiology was ischemic (29 patients, 69%) and 32 (79%) had another implanted device (24 ICD, 8 CRT-D). Twelve (29%) patients presented chronic atrial fibrillation (AF). Thirty-eight (90%) patients were treated with beta-blockers and 32 (76%) received sacubitril/valsartan (15) or ACE-inhibitors (17). A significant reduction in HF-related hospitalization has been observed after 6 and 12 months of CCM therapy, compared to the incidence in the 12 months before CCM implantation (Figure 1), with a relative risk reduction of 75% at 12 months (p<0.001). As shown in Figure 2, LVEF significantly improved both at 6 and 12-month follow up (p=0.042 and p=0.004, respectively), as well as MLWHFQ score (p=0.001 and p=0.032, respectively). The 6MWT distance did not show significant changes (6-month, p=0.252 and 12-month, p=0.281), mainly due to physical limitations in some patients. NYHA class improved significantly both at 6 (p=0.001) and 12-months (p=0.012), with 80% of patients showing an improvement of at least 1 class compared to baseline. After stratifying by HF aetiology, LVEF at 12-months improved significantly in non-ischaemic HF (p=0.028), while in patients with ischaemic aetiology improved significantly at 6-months (p=0.0416) but not at 12-months (p=0.135). Conclusion: CCM proved to be effective in improving symptoms, QoL and in reducing CHF-hospitalizations in patients with symptomatic CHF with reduced LVEF despite OMT. This prospective Italian Registry will be fundamental to gather more evidence, to assess the long-term effect of CCM, and also to measure the impact of CCM therapy in the Italian clinical practice.